2005
DOI: 10.1007/s10722-005-8313-8
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a core collection for maize germplasm preserved in Chinese National Genebank using geographic distribution and characterization data

Abstract: Since the 1980s, a large collection of maize has been preserved in the China National Genebank. To facilitate the evaluation and utilization of these valuable germplasm resources, a core collection was established. The collection was firstly divided into two groups, i.e. the landraces and inbred lines. The percentage of the original collection to be included in the core was given as 7% based on a previous study of sampling strategies in maize. Each group was sequentially stratified based on administrative prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 18 publications
2
42
0
3
Order By: Relevance
“…Considering this view, selection of one genotype having better traits along with additional criterion from each group/cluster was done. More or less similar strategies were also practices earlier by Singh et al (1991), Hu et al (2000), Cui et al (2004), Li et al (2004b) and Upadhyaya et al (2006). However, Wang et al (2007) also identified different evaluating parameters for rice core collection based on genotypic values and molecular marker information.…”
Section: Selection Of Core Collectionsmentioning
confidence: 55%
See 1 more Smart Citation
“…Considering this view, selection of one genotype having better traits along with additional criterion from each group/cluster was done. More or less similar strategies were also practices earlier by Singh et al (1991), Hu et al (2000), Cui et al (2004), Li et al (2004b) and Upadhyaya et al (2006). However, Wang et al (2007) also identified different evaluating parameters for rice core collection based on genotypic values and molecular marker information.…”
Section: Selection Of Core Collectionsmentioning
confidence: 55%
“…To identify the sub-groups, first all the genotypes were subjected to cluster analysis based on Mahalanobis" D 2 statistics for their representativeness (Cui et al, 2004) and then selection of core collections was improved through evaluating compositively (Singh et al, 1991), with sampling strategies based on genotypic/morphological values of the genotypes (Hu et al, 2000), comparing different genetic distances, cluster methods and sampling strategies methods (Xu et al, 2004), SSR marker base data (Zhang et al, 2011) and geographic distribution data (Li et al, 2004b).…”
Section: Core Collectionmentioning
confidence: 99%
“…The means of MD% and d -D% parameters were calculated for 10 000 simulated samples using each sampling strategy. A sampling strategy could be considered to be more effective in establishing a representative core subset of genetic diversity in the entire collection if the means of the traits in the cores and the entire collection were maintained at the same level (i.e., the mean MD% of the simulated samples was close to zero) and, simultaneously, when the overall variation in a core subset was greater than that in the entire collection (i.e., the mean d -D% across the results of the simulated samples was greater relative to that obtained for the simple random sampling strategy) (Hu et al 2000;Li et al 2004Li et al , 2005Franco et al 2005;Oliveira et al 2010). The explanation for this logic could be the following: the mean MD% for simulated core collections being close to zero indicates that, within a core subset, a minimum loss of the original diversity occurred; however, the mean d -D% across the results of the simulated core subsets being greater relative to that obtained for the simple random sampling strategy indicates that the frequency distribution in a core subset is more similar to a uniform distribution compared to that of the entire collection.…”
Section: Methodsmentioning
confidence: 99%
“…The efficiency evaluation of a sampling strategy involved validating the representativeness of the obtained core collection (Hu et al 2000;Li et al 2004;Wang et al 2007;Oliveira et al 2010). The representativeness of the original genetic diversity in the core collections was validated using the difference of means and a multivariate variation measure of traits in the core subsets and the entire collection (Li et al 2004(Li et al , 2005Franco et al 2005;Kim et al 2007; Figure 1. A schematic of the sampling strategies used for constructing core collections from the Polish orchardgrass germplasm collection Oliveira et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Kod kukuruza je formirano nekoliko core kolekcija u različitim regionima sveta: kolekcija uzoraka sa Kariba iz CIMMYT-ove (International Centre for Maize and Wheat Improvement) banke gena (Taba et al, 1998), lokalnih populacija iz Urugvaja (Malosetti i Abadie, 2001) i kineskih populacija (Li et al, 2004).…”
Section: Jezgrovne (Core) Kolekcijeunclassified